Peran Surau dalam Membentuk Sikap Inklusif dan Toleran Hamka terhadap Tradisi Lokal Minangkabau - Amelina, Naila; Soraya, Nyayu; Anggara, Baldi (Zawiyah: Jurnal Pemikiran Islam, 2025)
This article examines the role of surau education in shaping Buya Hamka's inclusive and tolerant attitude towards local Minangkabau traditions. Departing from the agenda of religious moderation and the importance of local wisdom, this study highlights a gap in research that has so far mostly discussed Hamka's moderation or Minangkabau surau separately. The study uses a qualitative approach with a literature study, combining historical-sociological and biographical-intellectual analysis of Hamka's educational journey, as well as content analysis of his works related to customs and Qur'anic interpretation. The results show, first, that Minangkabau surau education, including during its transformation into a madrasah, produced a configuration of monotheistic values, Sufism, morals, deliberation, and a balance between religion and custom that aligns with the concept of wasathiyah. Second, Hamka's attitude towards local traditions is both inclusive and exclusive: he embraced customs as a source of moral wisdom, but firmly committed to practices that violated justice and monotheism. Third, the values ​​and pedagogical mechanisms of the surau act as a foundation and “ethical anchor” that enable Hamka to combine intellectual openness with respect for local traditions, while also offering a conceptual model for the development of local wisdom-based Islamic education in contemporary Indonesia